Analisis Struktur Modal Dan Efektivitaspenggunaan Modal Kerja Pada Toko Megaloy SP 3 - Aloysius Danduru Pabendon; Daniel Nemba Dambe (STIE Jambatan Bulan, 2023)
This study aims to determine the impact of changes in capital composition, as well as the effectiveness of using working capital in Toko Megaloy. This research is a descriptive research with data collection techniques using observation, interview, and documentation techniques. The data analysis instruments used in this study are debt to asset ratio analysis, return on asset ratio, and working capital turn over ratio. The results of the analysis show that after changes in capital composition with the addition of debt in 2021 in TokoMegaloy, the debt to asset ratio is very good. The rate of return on assets where before changes in capital structure in the good category and after changes in capital structure there was an increase so that it was categorized as very good.working capital turn over ratio, it can be concluded from year to year the average working capital turnover is above the standard